Sistem Pengambilan Keputusan Pengguna Bahan Bakar Minyak (BBM) Jenis Pertamax di Kecamatan Tampan - Mifta Hidayat; Fery Wongso; Aris Ariyanto (INCODING: Journal of Informatics and Computer Science Engineering, 2021)
In general, SPBU (General Fuel Filling Station) sells the most widely used fuels such as premium, diesel or bio diesel, pertalite and pertamax. Pertamax fuel is fuel produced by adding additives in the processing process. These additives make combustion more complete so that the mixing process of fuel and air that enters the combustion chamber is more perfect. Pertamax contains 92 octane and no lead, resulting in a more environmentally friendly exhaust gas. Quantitative research is research that concentrates on testing theories through research variables in the form of numbers and then analyzes the data using statistical processes either manually or with computer software. In this study the authors used two data sources, namely: primary data and secondary data. Primary data is data obtained from the first source either from individuals or individuals such as the results of filling out a questionnaire that is usually done by researchers. The results of K Means clustering get the same results as the Rapidminer program, namely Cluster 0 = 106, Cluster 1 = 56, and Cluster 2 = 38. engine performance and many respondents were satisfied with the type of pertamax used. The type of Pertamax that respondents are interested in is Pertamax and the reasons for not wanting to queue up.